Masan Devi at Versova Koliwada - Mumbai Archive Project Team (Jio Institute, 2024)
Golden coconuts, covered in gold foil, are offered to Masan Devi for her blessings. Masan Devi is worshipped by the Koli community as the guardian deity of Versova Koliwada. The Masan Devi Temple is located in Versova.